CASTLEMAN DISEASE VARIANT OF POEMS SYNDROME. A CASE REPORT: SÍNDROME POEMS ASOCIADO A ENFERMEDAD DE CASTLEMAN. UN REPORTE DE CASO - Sotelo, Pedro Paolo (2019)
Introduction: POEMS (Polyneuropathy, Organomegaly, Endocrinopathy, Monoclonal protein, Skin changes) syndrome is a rare multisystem disorder. Castleman disease is an atypical lymphoproliferative disorder of unknown cause, which can be associated to POEMS. Clinical Case: This is the case of a 37-year-old patient with 2-year history of numbness and weakness in lower limbs associated to multiple adenopathy, skin hyperpigmentation and hypertrichosis. Electromyography showed active chronic sensory-motor polyneuropathy of axonal type; and serum electrophoresis showed a monoclonal band of A Immunoglobulin lambda type. Submaxillary lymph node biopsy was consistent with Castleman Disease. Conclusion: This report highlights the fact that Castleman Disease is frequent among patients with POEMS syndrome, constituting a significant variant, and should always be ruled out. Furthermore, plasmapheresis could be a useful alternative among patients with severe neurological symptoms.